Karakteristik Kepemimpinan dalam Pendidikan di Indonesia - Jannah, Alfia Miftakhul; Arni, Irada Haira; Fatwa, Bunga; Hanifah, Husnun; Akhmad, Fandi (Lembaga Yasin AlSys, 2021)
Leadership is needed to drive an organization. Leadership is the determining factor in the success of a program in education. It is necessary to underline the success of education is not the work of individuals, but the work of competent cooperation. Therefore, the leader must be able to give influence to his work team (leadership is influence) to work effectively and efficiently. The purpose of this research is to understand more deeply about the characteristics that must exist in a leader so that the leader can play his role optimally and the educational program can run smoothly. This research uses literary study methods in the form of several journals and leadership books. The results of this study show that after understanding the characteristics of an ideal leader, it should be adjusted to the leadership model to be chosen. All attitudes and behaviors of a leader must be able to build trust and confidence with his subordinates, because the leader is the bridge to the achievement of the organization's mission.